Historical Case of Cervical Penetrating Wound: From First Aid to Surgical Intervention - Koné Fatogoma Issa; Keïta Mohamed Amadou; Soumahoro Siaka; Konaté N’faly; Diarra Kassim; Timbo Samba Karim (Case Reports in Otolaryngology)
Objective. We report a case of cervical penetrating wound by posing the problem of its support and by analyzing the chain of survival of a patient to human sacrifice. Case Report. It was an 11-year-old boy admitted to the hosting service of cervical penetrating wound emergency occurring in a context of human sacrifice by weapon (knife). On admission, the conscious patient had a left cervical hematoma at the level of the cervical zone II and severe signs of acute anemia. The exploratory cervicotomy, carried out 12 hours after the trauma under transfusion, allowed us to highlight a section of the front edge of the sternocleidomastoid and previous jugular muscles under hyoid. We noted the presence of a linear wound of 1 cm at the level of the left internal jugular vein. The wound of the internal jugular vein has been repaired with the Prolene 4.O. The outcome was good, allowing the exit 10 days after cervicotomy. Conclusion. The causal circumstances of cervical penetrating wounds are diverse. Their importance or their severity depends on the causative circumstances dominated by aggression and attempts to autolysis. Human sacrifice, with use of the weapon, is an exceptional circumstance.